A synthetic heparin mimetic that allosterically inhibits factor XIa and reduces thrombosis in vivo without enhanced risk of bleeding. (10th September 2019) - Al‐Horani, Rami A.; Abdelfadiel, Elsamani I.; Afosah, Daniel K.; Morla, Shravan; Sistla, Jyothi C.; Mohammed, Bassem; Martin, Erika J.; Sakagami, Masahiro; Brophy, Donald F.; Desai, Umesh R.
Abstract: Background: Human factor XIa (FXIa) is an actively pursued target for development of safer anticoagulants. Our long‐standing hypothesis has been that allosterism originating from heparin‐binding site(s) on coagulation enzymes is a promising approach to yield safer agents. Objectives: To develop a synthetic heparin mimetic as an inhibitor of FXIa so as to reduce clot formation in vivo but not carry high bleeding risk. Methods: We employed a gamut of methods involving synthetic chemistry, biophysical biochemistry, enzyme assays, blood and plasma coagulation assays, and in vivo thrombosis models in this work. Results: Sulfated chiro‐inositol (SCI), a non‐saccharide mimetic of heparin, was synthesized in three steps in overall yields of >50%. SCI inhibited FXIa with potency of 280 nmol/L and preferentially engaged FXIa's heparin‐binding site to conformationally alter its active site. SCI inhibition of FXIa could be rapidly reversed by common antidotes, such as protamine. SCI preferentially prolonged plasma clotting initiated with recalcification, rather than thromboplastin, alluding to its intrinsic pathway‐based mechanism. Human blood thromboelastography indicated good ex vivo anticoagulation properties of SCI. Rat tail bleeding and maximum‐dose‐tolerated studies indicated that no major bleeding or toxicity concerns for SCI suggesting a potentially safer anticoagulation outcome. FeCl3 ‐induced arterial and thromboplastin‐induced venous thrombosis model studies in the rat showed reduced thrombus formation by SCI at 250 μg/animal, which matched enoxaparin at 2500 μg/animal. Conclusions: Overall, SCI is a highly promising, allosteric inhibitor of FXIa that induces potent anticoagulation in vivo. Further studies are necessary to assess SCI in animal models mimicking human clinical indications.